The last Mrs. Parrish : a novel - Constantine, Liv (New York : Harper, an imprint of HarperCollins Publishers, 2017)
"Amber Patterson is fed up. She$1 (Bs tired of being a nobody: a plain, invisible woman who blends into the background. She deserves more$1 (Ba life of money and power like the one blond-haired, blue-eyed goddess Daphne Parrish takes for granted. To everyone in the exclusive town of Bishops Harbor, Connecticut, Daphne$1 (Ba socialite and philanthropist$1 (Band her real-estate mogul husband, Jackson, are a couple straight out of a fairy tale. Amber$1 (Bs envy could eat her alive . . . if she didn't have a plan. Amber uses Daphne$1 (Bs compassion and caring to insinuate herself into the family$1 (Bs life$1 (Bthe first step in a meticulous scheme to undermine her. Before long, Amber is Daphne$1 (Bs closest confidante, traveling to Europe with the Parrishes and their lovely young daughters, and growing closer to Jackson. But a skeleton from her past may undermine everything that Amber has worked towards, and if it is discovered, her well-laid plan may fall to pieces."--s
Keywords: Single women -- Fiction; Manipulative behavior -- Fiction; Swindlers and swindling -- Fiction; Rich people -- Fiction; Connecticut -- Fiction; Psychological fiction; Thrillers (Fiction)